El libro de los pequeños milagros ... - Muñoz Rengel, Juan Jacinto, 1974- (Madrid : Editorial Páginas de Espuma, 2016)
Part bestiary, part theology manual, part science fiction, part catalog of wonders--this collection of one hundred micronarratives chronicles various entities and events spanning from the city to outer space.
Includes index.
Online resource; title from ePub title page (Digitalia, viewed February 10, 2018)
Keywords: Flash fiction; Short stories; Electronic books